Susceptibility-diffusion mismatch in middle cerebral artery territory acute ischemic stroke: clinical and imaging implications. (July 2017) - Payabvash, Seyedmehid; Taleb, Shayandokht; Benson, John C; Hoffman, Benjamin; Oswood, Mark C; McKinney, Alexander M; Rykken, Jeffrey B
Background: Recent studies have suggested a correlation between susceptibility–diffusion mismatch and perfusion–diffusion mismatch in acute ischemic stroke patients. Purpose: To determine the clinical and imaging associations of susceptibility-diffusion mismatch in patients with acute ischemic stroke in the middle cerebral artery (MCA) territory. Material and Methods: Consecutive patients with MCA territory acute ischemic stroke, who had magnetic resonance imaging (MRI) performed with susceptibility-weighted imaging (SWI) and diffusion-weighted imaging (DWI) within 24 h of symptom onset or time last-seen-well, were included. Two neuroradiologists reviewed SWI scans for SWI–DWI mismatch defined by regionally increased vessel number or diameter on SWI extending beyond the DWI hyperintensity territory in the affected hemisphere. The stroke severity at admission was evaluated using the National Institutes of Health Stroke Scale (NIHSS) score. Poor clinical outcome was defined by a 3-month modified Rankin Scale (mRS) score >2. Results: The SWI–DWI mismatch was identified in 44 (29.3%) of 150 patients included in this study. Patients with SWI–DWI mismatch had smaller admission infarct volumes (31.2 ± 44.7 versus 55.9 ± 117.7 mL, P  = 0.045) and were younger (60.4 ± 18.9 versus 67.1 ± 15.5, P  = 0.026). After correction for age, admission NIHSS score, and infarct volume, the SWI–DWI mismatch was associated with a 22.6% lower rate of poor clinical outcome using propensity score matching ( P  = 0.032). In our cohort, thrombolytic therapy showed no significant effect on outcome. Conclusion: The presence of SWI–DWI mismatch in acute MCA territory ischemic infarct is associated with smaller infarct volume. Moreover, SWI–DWI mismatch was associated with better outcome after correction for infarct size, severity of admission symptoms, and age.